Reflecting talks: a pedagogical model in the learning organization. Issue 2 (4th March 2019) - Arnesson, Kerstin; Albinsson, Gunilla
ABSTRACT: The aim of the article is to deepen the understanding of how a pedagogical model for reflecting talks can be used in order to make sustainable learning part of the daily work in the learning organization. From an interactive research approach, we have together with a project management group in a European Social Fund project worked with sustainable learning and knowledge development. Empirical data has been collected at the implementation of ten reflecting talks about sustainable equality. The results of the study lead to a strategy for how sustainable learning can become part of the daily work at a workplace. The strategy is constituted by a pedagogical model for reflecting talks, which clearly shows how sustainable learning in an organization can be structured. The core of the pedagogical model for the reflecting talks where both practically applied and theoretically anchored knowledge are important components. The learning process is based on observation, reflection, analysis and discussion of concrete situations/events. The models rests on four basic conditions; pedagogical competence, a delimited problem area, the learning group and timeframes. The model can be used in the daily work at short dialogues or at more penetrating discussions.